2013
DOI: 10.1016/j.amjcard.2013.03.051
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for Hemorrhage Among Warfarin Recipients Prescribed Amiodarone

Abstract: Amiodarone inhibits the hepatic metabolism of warfarin, potentiating its anticoagulant effect. However, the clinical consequences of this are not well established. Our objective in this study was to characterize the risk of hospitalization for a hemorrhage associated with the initiation of amiodarone within a cohort of continuous warfarin users in Ontario. We conducted a population-based retrospective cohort study among Ontario residents aged ≥66 years receiving warfarin. Among patients with at least 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
0
17
0
1
Order By: Relevance
“…The primary safety end point was the occurrence of a major bleeding event using primary hospital discharge diagnosis codes including intracranial hemorrhage, major gastrointestinal bleeding, and other major bleeding events (). Defining major bleeding events based on inpatient claims was previously found to have a PPV between 89% and 98% . The secondary study outcome was the occurrence of minor bleeding events presenting on outpatient encounter claims using a primary or secondary diagnosis (i.e., those not requiring hospitalization).…”
Section: Methodsmentioning
confidence: 99%
“…The primary safety end point was the occurrence of a major bleeding event using primary hospital discharge diagnosis codes including intracranial hemorrhage, major gastrointestinal bleeding, and other major bleeding events (). Defining major bleeding events based on inpatient claims was previously found to have a PPV between 89% and 98% . The secondary study outcome was the occurrence of minor bleeding events presenting on outpatient encounter claims using a primary or secondary diagnosis (i.e., those not requiring hospitalization).…”
Section: Methodsmentioning
confidence: 99%
“…While it is acknowledged that not all interacting drugs induce a DME phenoconversion, many of these nonphenoconverting drugs have a pharmacodynamic effect on the clinical outcome of interest (bleeding in the case of warfarin), thereby further prejudicing the conclusions from association studies. Amiodarone inhibits CYP2C9, and Lam et al [80] reported that overall, 56 (0.8%) amiodarone recipients and 23 (0.3%) control patients receiving warfarin were hospitalized for haemorrhage within 30 days of initiating amiodarone (adjusted hazard ratio 2.45, 95% CI 1.49-4.02). Seven of 56 (12.5%) patients hospitalized for a haemorrhage after starting amiodarone died in hospital.…”
Section: Genotype-dependent Susceptibility To Phenoconversionmentioning
confidence: 99%
“…Other studies have assessed the risk of bleeding or risk of hospitalization for haemorrhage due to drug interactions with warfarin. [7][8][9][10][11] A recent approach employed in a small number of studies that investigate warfarin drug-drug interactions is the use of real-world data from administrative databases. This approach allows the identification of the frequency of concurrent use of warfarin with other drugs and quantification of the combined treatment effect on INR values and has provided clinically highly useful information.…”
Section: Introductionmentioning
confidence: 99%